The diagnosis of anti-LGI1 encephalitis varies with the type of immunodetection assay and sample examined - Muñoz-Sánchez, Guillermo; Planagumà, Jesús; Naranjo, Laura; Couso, Rocío; Sabater, Lidia; Guasp, Mar; Martínez-Hernández, Eugenia; Graus, Francesc; Dalmau, Josep; Ruiz-García, Raquel (Frontiers in Immunology, 2022)
Detection of Leucine-rich glioma inactivated 1 (LGI1) antibodies in patients with suspected autoimmune encephalitis is important for diagnostic confirmation and prompt implementation of immunomodulatory treatment. However, the clinical laboratory diagnosis can be challenging. Previous reports have suggested that the type of test and patient’s sample (serum or CSF) have different clinical performances, however, there are no studies comparing different diagnostic tests on paired serum/CSF samples of patients with anti-LGI1 encephalitis. Here, we assessed the clinical performance of a commercial and an in house indirect immunofluorescent cell based assays (IIF-CBA) using paired serum/CSF of 70 patients with suspected anti-LGI1 encephalitis and positive rat brain indirect immunohistochemistry (IIHC). We found that all (100%) patients had CSF antibodies when the in house IIF-CBA was used, but only 88 (83%) were positive if the commercial test was used. In contrast, sera positivity rate was higher with the commercial test (94%) than with the in house assay (86%). If both serum and CSF were examined with the commercial IIFA-CBA, 69/70 (98.5%) patients were positive in at least one of the samples. These findings are clinically important for centers in which rat brain IIHC and in house IIFA-CBA are not available. Moreover, the observation that all patients with anti-LGI1 encephalitis have antibodies in CSF is in line with the concept that these antibodies are pathogenic.